Transcriptomic Identification of Core Regulatory Genes for Higher Alcohol Production in Saccharomyces cerevisiae at Different Sugar Concentrations in Wine Fermentation - Lu Chen; Xiaona Ren; Yanan Wang; Dongshu Hao; Yanying Liang; Yi Qin (Foods)
Higher alcohols are significant flavor compounds in wine, and the elevated sugar content in grape raw materials has a substantial impact on wine quality. This study investigates the effect of high sugar content on the production of higher alcohols in wine and elucidates the underlying mechanisms through transcriptome analysis. The results indicate that sugar concentrations of 240 g/L and 280 g/L lead to increases in higher alcohol content of 17% and 24%, respectively. Transcriptome sequencing was employed to analyze differentially expressed genes at various fermentation stages, which resulted in the identification of the GRE3 gene. It was determined that the expression level of GRE3 significantly influences higher alcohol content. Knocking out GRE3 using molecular methods led to a notable 17.76% decrease in higher alcohol yield at a sugar concentration of 240 g/L, representing a novel finding not previously documented in the literature. This research provides valuable insights into the influence of high-sugar grape materials on the production of higher alcohols by Saccharomyces cerevisiae and the associated mechanisms.